Analysis of the Physical and Mechanical Behavior of Soil Reinforced with Banana Fibers - Favio Osmar Schreiber Robles; Socrates Pedro Muñoz Pérez; Juan Martin Garcia Chumacero; Elver Sanchez Diaz; Carlos Arturo Damiani Lazo; Juan De Dios Malpartida Iturregui; Angel Antonio Ruiz Pico; Edwin Adolfo Diaz Ortiz; Ernesto Dante Rodríguez Lafitte; Ana Paula Bernal Izquierdo (Ingeniería)
Context: Soils reinforced with natural fibers such as banana fibers (BF) constitute a promising alternative for improving the geotechnical properties of the soil, especially in rapidly growing urban contexts like Peru.